Pengaruh Model Pembelajaran Game Based Learning (GBL) Menggunakan Media Kuis Family 100 Berbasis Digital Canva terhadap Hasil Belajar Siswa Kelas VII pada Mata Pelajar IPA di SMP Negeri 4 Samarinda - Meisuari Indah Permata Sari; Jailani Jailani; Elsje Theodora Maasawet; Sonja Verra Tinneke Lumowa (UNIB Press, 2026)
The rapid development of educational technology requires innovative learning approaches to improve students' learning outcomes; however, the implementation of Game Based Learning (GBL) is still rarely applied in science learning at SMP Negeri 4 Samarinda. This study aimed to determine the effect of the Game Based Learning (GBL) model using a Canva-based digital Family 100 quiz on the learning outcomes of seventh-grade students on the topic of organization of life. The study employed a quasi-experimental method with a pretest-posttest non-equivalent control group design involving 50 students. The results showed that the average post-test score of the experimental class was higher than that of the control class, and the Independent Sample t-test yielded a significance value of 0.022 (<0.05). Therefore, the Game Based Learning (GBL) model using a Canva-based digital Family 100 quiz had a significant effect on students' learning outcomes and can be used as an alternative interactive and innovative learning approach.